Odpowiedź :
Odpowiedź:
e)
[tex]\frac{1}{x} = \frac{5}{2x+1} \\2x+1=5x\\2x-5x=-1\\-3x=-1\\x=\frac{1}{3} \\x\neq 0\\x\neq -\frac{1}{2}[/tex]
f)
[tex]\frac{-x}{2x-4} =\frac{3x}{1-6x} \\-x*(1-6x)=3x*(2x-4)\\-x+6x^{2} =6x^{2} -12x\\-x=-12x\\-x+12x=0\\11x=0\\x=0\\x\neq 2\\x\neq \frac{1}{6}[/tex]
[tex]\frac{1}{x} =\frac{5}{2x+1} \\x\neq 0\land2x+1\neq 0\to x\neq -\frac{1}{2} \\D=R\backslash\{0,-\frac{1}{2} \}\\2x+1=5x\\2x-5x=-1\\-3x=-1 |:(-3)\\\boxed{x=\frac{1}{3} }[/tex]
[tex]\frac{-x}{2x-4} =\frac{3x}{1-6x} \\2x-4\neq 0\to2x\neq 4|:2\to x\neq 2\\1-6x\neq 0\to-6x\neq -1\to x\neq \frac{1}{6} \\D=R\backslash\{2,\frac{1}{6} \}\\-x(1-6x)=3x(2x-4)\\-x+6x^2=6x^2-12x\\6x^2-6x^2=x-12x\\-11x=0 |:(-11)\\\boxed{x=0}[/tex]